Health Indicators for Accelerating Stunting Reduction: Family Practices in Indonesian Borderland - Rua, Yusfina Modesta; Nahak, Maria Paula Marla (Journal of Maternal and Child Health, 2024)
Background: The Indonesian government has established the latest family-based approach to implement the national strategy to accelerate the reduction of stunting in Indonesia through a family-based intervention approach. Family-based intervention is proven scientifically efective in preventing growth retardation in children under five. However, this research was conducted on families with children aged 0-2 years so that all of the presented problems can be used as a reference in providing family-based interventions. This study aims to describe family health practices in preventing stunting among the people in the border areas of Indonesia and Timor Leste. Subjects and Method: This was a quantitative descriptive study with a cross-sectional design, conducted from May to June 2022. A total of 257 families (out of a total population of 566) with children aged 0-24 months spread across 16 integrated healthcare centers (Posyandu) at the Haliwen Health Center, Belu District, East Nusa Tenggara Province, Indonesia. The subjects in this study were selected by simple random sampling. The single variable in this study was family health practices in preventing stunting, consists of 18 indicators adopted and elaborated from presidential regulation 72 concerning accelerating the reduction of stunting. the data collected by a set of questionnaires. The data analyze by univariate analysis to describe frequency (n) and percentage (%) of each indicators. Results: Out of a total of 18 assessed indicators, most families still use open garbage cans, burning garbage for destruction, and did not carry out pre-marital health screening. Conclusion: The results of this study showed that most of the health indicators had been carried out by families with infants under two years old. It is in line with the growth status of under-two, most of whom are not stunted. Keywords: stunting, children under two, family-based intervention. Correspondence: Maria Paula Marla Nahak. Nursing study program, Universitas Timor, Indonesia. Jln. El Tari - Km. 09, Sasi, Kefamenanu, Timor Tengah Utara, Nusa Tenggara Timur, Indonesia. Email: paulamarla@unimor.ac.id.